Agronomic Response of Various Rice Varieties Using Nano Priming ZnO Treatment on Seeds to Drought Stress - Anita Natalia; Iin Siti Aminah; Neni Marlina (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice (Oryza sativa L.) is a staple food crop that is being promoted as part of efforts to enhance national food security. The utilization of dry land in Indonesia is one mechanism that supports this food security initiative. Seed priming treatments have been shown to improve plant tolerance to drought stress conditions. This adaptation study aims to investigate the differences in seed viability among several rice varieties subjected to different concentrations of ZnO nanopriming, as well as the performance of selected seeds grown under drought stress conditions during the vegetative phase of the plants. The first phase of the research involved seed screening and variety selection, accompanied by seed priming treatments. The experimental design employed was a Factorial Randomized Block Design, with the first factor being ZnO concentrations of 0 ppm, 10 ppm, 15 ppm, and 20 ppm. The second factor involved the selection of four rice varieties: Ciherang, Inpari 32 HDB, Mekongga, and the expired Ciherang. The second phase of the research built upon the first phase, utilizing the best rice seeds identified from the screening results along with the most effective priming treatment. These seeds were subjected to drought stress treatments (without watering), which included 0 HTS, 5 HTS, 7 HTS, and 14 HTS. The results indicated that the seed priming treatment with ZnO nanoparticles (NPs) significantly increased the germination percentage of rice seeds across all varieties, with the optimal treatment combinations being 30 ppm for the Ciherang variety and 100 ppm for the Mekongga variety. Under drought stress conditions, the Ciherang variety at 30 ppm exhibited the best adaptation up to 14 HTS. Overall, the application of nano-priming with ZnO NPs enhanced seed germination and promoted plant growth.